Gradient cathode catalyst layer, membrane electrode and proton exchange membrane fuel cell
By designing a gradient cathode catalytic layer in a large-area proton exchange membrane fuel cell, the problem of uneven distribution of oxygen and water vapor is solved, and the uniformity of physical field distribution and life extension in the fuel cell are achieved.
Patent Information
- Application Number
- CN202411502649.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
AI Technical Summary
In large-area proton exchange membrane fuel cells, the physical field distribution caused by uneven oxygen concentration and water vapor distribution affects the service life of the fuel cell.
Design a gradient cathode catalytic layer, including three aliquots of catalytic zones, the Pt load and the mass ratio of ionomer to carbon support are increased and decreased in turn, and the gradient structure is formed by spraying catalyst slurry of different proportions to improve gas Flow and distribution.
It improves the uniformity of physical field distribution in the fuel cell plane, extends the service life of the fuel cell, and reduces the difficulty of preparation.
Smart Images

Figure CN119252937A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a gradient cathode catalyst layer, a membrane electrode and a proton exchange membrane fuel cell. Background Art
[0002] Proton exchange membrane fuel cells are electrochemical devices that use hydrogen as fuel. The cathode and anode catalyst layers carry out oxygen reduction reactions and hydrogen oxidation reactions respectively. In the process of converting chemical energy into electrical energy, no air pollutants are produced, so they show broad development prospects. At present, each cell of a commercial fuel cell stack is usually designed to be 100 to 500 cm 2 The effective active area of the fuel cell can meet the needs of high-power applications. However, a large membrane electrode will bring about significant uneven distribution of physical fields such as water-heat-electricity, which will in turn affect the service life of the fuel cell.
[0003] The gradient design of the cathode catalyst layer can effectively improve the distribution characteristics of the above physical field, thereby extending the battery life. CN117438596A discloses a method for preparing a gradient catalyst layer membrane electrode, by spraying catalyst slurries of different proportions on the proton exchange membrane in sequence, forming a platinum loading gradient that gradually decreases in the thickness direction from the proton exchange membrane to the gas diffusion layer, a perfluorosulfonic acid content gradient, a graphite carbon content gradient, and a gradually increasing carbon nanofiber content gradient, so as to respectively increase the oxygen reduction reaction rate, proton conduction rate, liquid water discharge rate, and oxygen diffusion rate, thereby improving the membrane electrode performance. CN113991126A discloses a gradient proton exchange membrane fuel cell membrane electrode, its preparation method, and application. The first catalyst layer of the cathode and anode is distributed on both sides of the proton exchange membrane, with the highest ionomer content and the lowest platinum content, which reduces the interface effect of the membrane electrode; the second catalyst layer has the highest platinum content, and the lowest ionomer content and EW value; the cathode is equipped with a third catalyst layer, whose platinum content is lower than the second catalyst layer, and the ionomer content is reduced, and the ionomer EW value is increased to prevent flooding caused by excessive reaction gas concentration and too fast reaction. Thus, a three-stage cathode and two-stage anode gradient catalyst layer is formed, which improves the uniformity of gas distribution and platinum utilization.
[0004] However, the above-mentioned prior art only considers the gradient design in the thickness direction of the catalyst layer, and does not consider the in-plane direction. For the application scenarios of large-area proton exchange membrane fuel cells, such as fixed power stations, higher requirements are placed on the life of the fuel cell. Because in a large-area flow field, along the direction of the flow channel, the oxygen concentration becomes lower and the water vapor concentration becomes higher, resulting in an increase in the water content of the membrane, which causes the catalyst oxygen adsorption rate and proton conduction rate to show very large differences in the plane. Therefore, the flow and distribution of gas in the in-plane direction of the large-area fuel cell are more uneven, which in turn leads to a more uneven distribution of physical fields such as water-heat-electricity.
[0005] Therefore, it is urgent to develop a new type of fuel cell cathode catalyst layer that can effectively improve the physical field distribution within the fuel cell plane so as to be applied to large-area proton exchange membrane fuel cells. Summary of the invention
[0006] The purpose of the present invention is to provide a gradient cathode catalyst layer, a membrane electrode and a proton exchange membrane fuel cell in order to overcome the defect of the prior art that the physical field distribution in the plane of a large-area fuel cell cannot be improved.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The present invention provides a gradient cathode catalyst layer, comprising three equally divided catalyst zones arranged in parallel in sequence, wherein the three equally divided catalyst zones are defined as a first catalyst zone, a second catalyst zone and a third catalyst zone in sequence along a gas flow direction;
[0009] The first catalytic zone, the second catalytic zone and the third catalytic zone all include Pt / C catalyst and ionomer, the Pt loading in the first catalytic zone, the second catalytic zone and the third catalytic zone increases successively, and the mass ratio of ionomer to carbon carrier (i.e., I / C ratio) decreases successively.
[0010] Furthermore, the average Pt loading of the first catalytic zone, the second catalytic zone and the third catalytic zone is 0.15-0.25 mg / cm 2 , preferably 0.2 mg / cm 2 ; The Pt loading in the three catalytic zones is between 0.1 and 0.3 mg / cm 2 The range is incremented in sequence.
[0011] Furthermore, the average mass ratio of the ionomer to the carbon carrier in the first catalytic zone, the second catalytic zone and the third catalytic zone is 0.5-0.7, preferably 0.6; the mass ratio of the ionomer to the carbon carrier in the three catalytic zones decreases successively in the range of 0.4-0.8.
[0012] Furthermore, the gradient cathode catalyst layer is prepared by the following method:
[0013] The active area of the proton exchange membrane is divided into three equal parts to form a first catalytic zone, a second catalytic zone and a third catalytic zone in sequence; three portions of catalyst slurries C1, C2 and C3 are prepared respectively, the Pt loading in the three portions of the catalyst slurries increases successively, and the mass ratio of the ionomer to the carbon carrier decreases successively; the three portions of the catalyst slurries are sprayed onto the first catalytic zone, the second catalytic zone and the third catalytic zone respectively, to obtain the gradient cathode catalytic layer.
[0014] Furthermore, in step S1, the active area of the proton exchange membrane is 100-500 cm 2 .
[0015] Furthermore, in step S2, the catalyst slurry includes Pt / C catalyst and ionomer.
[0016] Furthermore, the mass fraction of Pt in the Pt / C catalyst is 20-60% and increases successively in the three catalyst slurries C1, C2 and C3.
[0017] Furthermore, the mass ratio of the ionomer to the carbon carrier is 0.4-0.8 and decreases successively in the three catalyst slurries C1, C2 and C3.
[0018] Furthermore, the preparation method of the catalyst slurry comprises the following steps: weighing Pt / C catalyst and ionomer solution in proportion, adding ethanol aqueous solution and mixing evenly, and then ball milling and dispersing to obtain the catalyst slurry.
[0019] Furthermore, the ball milling time is 6-24 hours, preferably 12-18 hours.
[0020] Furthermore, the rotation speed of the ball mill is 100-300 rpm, preferably 150 rpm.
[0021] Furthermore, the dispersion is carried out by ultrasonic dispersion, and the ultrasonic dispersion time is 10-60 min, preferably 20-30 min.
[0022] The present invention also provides a membrane electrode, which comprises a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively arranged on both sides of the proton exchange membrane; wherein the cathode catalyst layer adopts the above-mentioned gradient cathode catalyst layer.
[0023] Furthermore, the Pt loading of the anode catalyst layer is 0.1 mg / cm 2 , the thickness of the proton exchange membrane is 18-50μm.
[0024] The present invention also provides a proton exchange membrane fuel cell, which comprises the above membrane electrode.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) In view of the uneven flow and distribution of gas in a large-area flow field, the present invention makes a corresponding gradient design of Pt loading and I / C ratio in the inner direction of the cathode catalytic layer, thereby balancing the uneven current density distribution caused by the low concentration of reaction gas and the high concentration of water vapor at the gas outlet.
[0027] (2) In order to solve the problem that the oxygen concentration decreases significantly along the flow direction, causing the catalyst to significantly reduce its oxygen adsorption rate, the present invention performs a zoned design for the Pt loading in the inner direction of the cathode catalytic layer, and the Pt loadings in the three catalytic zones increase gradually.
[0028] (3) In order to solve the problem that the water vapor concentration increases significantly along the flow direction, causing the membrane water content to be too high, thereby significantly accelerating the proton conduction rate compared to the gas inlet area, the present invention divides the I / C ratio in the inner direction of the cathode catalytic layer into zones, and the I / C ratios of the three catalytic zones decrease.
[0029] (4) The present invention divides the cathode catalyst layer into three areas, which has a better uniformity of current density distribution than the catalyst layer that is uniformly distributed (i.e., there is only one catalytic area) and sprayed in two equally divided catalytic areas. The zoning design of more than three areas will increase the difficulty of preparing the catalyst layer. Therefore, the present invention has the advantages of both improving the uniformity of physical field distribution and reducing the difficulty of preparation.
[0030] (5) The present invention can greatly improve the gas flow rate at a level greater than 100 cm by designing the gradient of Pt loading and I / C ratio in the in-plane direction. 2 The flow uniformity in a large-area flow field can be improved, so it can be widely used in application scenarios of large-area proton exchange membrane fuel cells such as fixed power stations to extend the service life of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the structure of the gradient cathode catalyst layer of the present invention.
[0032] Figure 2 The fuel cell of Example 1 is at 1200 mA·cm -2 CFD simulation distribution of current density within the lower proton membrane surface.
[0033] Figure 3 The fuel cell of Comparative Example 1 is at 1200 mA·cm -2 CFD simulation distribution of current density within the lower proton membrane surface. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0035] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0036] Embodiment 1:
[0037] This embodiment provides a 105cm 2 The large-area fuel cell gradient cathode catalyst layer and the resulting membrane electrode and fuel cell are specifically prepared in the following steps:
[0038] (1) Prepare three catalyst slurries, namely C1, C2, and C3.
[0039] The preparation process of catalyst slurry C1 is as follows: weigh 1g of Pt / C catalyst (Pt mass fraction 30%) and 2.625g of Nafion solution (equivalent mass is 1100g / mol, ionomer mass fraction is 20%), put them into a ball mill bottle, and weigh 39.6ml of deionized water and 301.0ml of ethanol, also put them into the ball mill bottle, and mix them with the catalyst and Nafion solution. Tighten the ball mill bottle, place it on a ball mill and mill it for 12h, and the speed of the ball mill is 150rpm. Finally, before spraying, place the ball mill bottle in an ultrasonic cleaner (ultrasonic power is 150W) for 30min of ultrasonication to obtain catalyst slurry C1.
[0040] The preparation process of catalyst slurry C2 is as follows: weigh 1g of Pt / C catalyst (Pt mass fraction 40%) and 1.8g of Nafion solution (ionomer mass fraction 20%), put them into a ball mill bottle, and weigh 39.6ml of deionized water and 301.0ml of ethanol, also put them into the ball mill bottle, and mix them with the catalyst and Nafion solution. Tighten the ball mill bottle, place it on a ball mill and mill it for 12h, and the speed of the ball mill is 150rpm. Finally, before spraying, place the ball mill bottle in an ultrasonic cleaner (ultrasonic power of 150W) for 30min to obtain catalyst slurry C2.
[0041] The preparation process of catalyst slurry C3 is as follows: weigh 1g of Pt / C catalyst (Pt mass fraction 50%) and 1.125g of Nafion solution (ionomer mass fraction 20%), put them into a ball mill bottle, and weigh 39.6ml of deionized water and 301.0ml of ethanol, also put them into the ball mill bottle, and mix them with the catalyst and Nafion solution. Tighten the ball mill bottle, place it on a ball mill and mill it for 12h, and the speed of the ball mill is 150rpm. Finally, before spraying, place the ball mill bottle in an ultrasonic cleaner (ultrasonic power of 150W) for 30min to obtain catalyst slurry C3.
[0042] (2) In the sprayer setting, the spraying area is evenly divided into three parts, each part has an area of 35cm 2 The proton exchange membrane sprayed with the anode catalyst layer was laid flat on the sprayer. The Pt loading of the anode catalyst layer was 0.1 mg / cm 2, the thickness of the proton exchange membrane is 50μm. The anode slurry preparation process is as follows: weigh 1g of Pt / C catalyst (Pt mass fraction 40%), 1.8g of Nafion solution (ionomer mass fraction 20%), put them into a ball milling bottle, and weigh 39.6ml of deionized water and 301.0ml of ethanol, also put them into the ball milling bottle, and mix them with the catalyst and Nafion solution. Tighten the ball milling bottle, place it on a ball mill and mill it for 12h, and the speed of the ball milling is 150rpm. Finally, before spraying, place the ball milling bottle in an ultrasonic cleaner (ultrasonic power of 150W) for 30min to obtain the anode catalyst layer slurry.
[0043] (3) Spray the catalyst slurry C1 to the first catalytic zone, and clean the sprayer pipe after completion. Then spray the catalyst slurry C2 to the second catalytic zone, and clean the sprayer pipe after completion. Finally, spray the catalyst slurry C3 to the third catalytic zone, and clean the sprayer pipe after completion. Among them, the slurry spraying speed is 0.3ml / min, the spraying path is S-shaped, the heating plate temperature is 60°C, the number of spray layers is divided into 4 layers, and the Pt loadings of the first catalytic zone, the second catalytic zone, and the third catalytic zone are 0.15mg / cm 2 , 0.2mg / cm 2 , 0.25mg / cm 2 At the same time, because the quality of Nafion solution has been regulated in the slurry, the I / C ratio of the first catalytic zone, the second catalytic zone, and the third catalytic zone will automatically form a gradient distribution of 0.75, 0.6, and 0.45. The number of spray layers of the anode catalyst layer is 2, and the Pt loading is 0.1 mg / cm 2 .
[0044] Through the above steps, the active area of the membrane electrode can be sprayed, and finally a membrane electrode containing a gradient cathode catalyst layer can be obtained. The prepared membrane electrode is matched with AvCarb's GDS3250 carbon paper, and can be further assembled into a single cell for subsequent testing.
[0045] Comparative Example 1:
[0046] This comparative example provides a 105cm 2 The uniform cathode catalyst layer of the fuel cell and the finally prepared membrane electrode and fuel cell are prepared in the following specific steps:
[0047] The C2 catalyst slurry was prepared by referring to the preparation process of the C2 catalyst slurry in Example 1. The proton exchange membrane sprayed with the anode catalyst layer was laid flat on the sprayer. The Pt loading of the anode catalyst layer was 0.1 mg / cm 2 The thickness of the proton exchange membrane is 50 μm. The catalyst slurry C2 is evenly sprayed on the active area of the entire membrane electrode, and the Pt loading of the cathode catalyst layer is 0.2 mg / cm 2, I / C ratio is 0.6. The prepared membrane electrode is matched with AvCarb's GDS3250 carbon paper, and can be further assembled into a single cell for subsequent testing.
[0048] The present invention performs the following performance tests on Example 1 and Comparative Example 1: 100% humidity hydrogen is introduced into the anode, 100% humidity air is introduced into the cathode, the cathode back pressure is 50 kPa, the anode stoichiometric ratio is 1.2, the cathode stoichiometric ratio is 2, and the cooling inlet temperature is 70° C. The polarization curve test is in constant voltage mode, a step size of 0.05 V is used to test one current point, each point is stabilized for 1 minute, and the polarization curve is recorded. The results are shown in Table 1.
[0049] Table 1
[0050]
[0051] From the results in Table 1, the performance of Example 1 is comparable to that of Comparative Example 1, and is almost the same. Computational fluid dynamics (CFD) was used to introduce heat transfer, mass transfer, and electrochemical equations for numerical simulation. The boundary conditions were the same as the above test conditions. Other simulation parameters are shown in Table 2.
[0052] Table 2
[0053]
[0054]
[0055] The simulation results are as follows Figure 2-3 As shown, the fuel cell prepared by Example 1 has a current density at the air inlet and outlet positions that decreases and increases respectively, and approaches the current density in the middle area, compared with the fuel cell prepared by Comparative Example 1. The color change of the cloud map is smooth, and the uniformity of the current distribution in the proton membrane surface direction is significantly improved.
[0056] Current density distribution uniformity U i It can be calculated by the following formula:
[0057]
[0058] Where i is the current density at each point, i ave is the average current density, A MEA According to the above formula, the uniformity of the in-plane current density of the fuel cell proton membrane of Example 1 rises to 0.952, wherein the standard deviation of the current density along the air flow direction decreases by 16%, while the uniformity of the in-plane current density of the fuel cell proton membrane of Comparative Example 1 is 0.938.
[0059] In summary, the present invention successfully prepares a gradient cathode catalyst layer suitable for a large-area proton exchange membrane fuel cell for a large-area flow field, and divides the membrane electrode active area into three regions for separate design. The oxygen concentration near the gas inlet area (the first catalytic zone) is high, the water vapor concentration is low, and the membrane water content is low, so the Pt loading is reduced and the I / C ratio is increased, and a denser proton conduction path is constructed while balancing the catalyst adsorption rate of oxygen. The oxygen concentration near the gas outlet area (the third catalytic zone) is low, the water vapor concentration is high, and the membrane water content is high, so the Pt loading is increased and the I / C ratio is reduced, and the proton conduction rate is balanced while increasing the catalyst adsorption rate of oxygen. The middle area (the second catalytic zone) serves as a transition area, and cooperates with the first and third catalytic zones to form a cathode catalyst layer with a gradient distribution of Pt loading and I / C ratio in the in-plane direction, which ultimately improves the uniformity of current density distribution.
[0060] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A gradient cathode catalyst layer, characterized in that: It comprises three equally divided catalytic zones arranged in parallel in sequence, and the three equally divided catalytic zones are defined as a first catalytic zone, a second catalytic zone and a third catalytic zone in sequence along the gas flow direction; The first catalytic zone, the second catalytic zone and the third catalytic zone all include Pt / C catalyst and ionomer, the Pt loading in the first catalytic zone, the second catalytic zone and the third catalytic zone increases successively, and the mass ratio of ionomer to carbon carrier decreases successively.
2. A gradient cathode catalyst layer according to claim 1, characterized in that: The average Pt loading of the first catalytic zone, the second catalytic zone and the third catalytic zone is 0.15-0.25 mg / cm 2 The Pt loading in the three catalytic zones is between 0.1 and 0.3 mg / cm 2 The range is incremented in sequence.
3. A gradient cathode catalyst layer according to claim 1, characterized in that: The average mass ratio of the ionomer to the carbon carrier in the first catalytic zone, the second catalytic zone and the third catalytic zone is 0.5-0.7, and the mass ratio of the ionomer to the carbon carrier in the three catalytic zones decreases successively in the range of 0.4-0.
8.
4. A gradient cathode catalyst layer according to claim 1, characterized in that: The gradient cathode catalyst layer is prepared by the following method: The active area of the proton exchange membrane is divided into three equal parts to form a first catalytic zone, a second catalytic zone and a third catalytic zone in sequence; three portions of catalyst slurries C1, C2 and C3 are prepared respectively, the Pt loading in the three portions of the catalyst slurries increases successively, and the mass ratio of the ionomer to the carbon carrier decreases successively; the three portions of the catalyst slurries are sprayed onto the first catalytic zone, the second catalytic zone and the third catalytic zone respectively, to obtain the gradient cathode catalyst layer.
5. A gradient cathode catalyst layer according to claim 4, characterized in that: The catalyst slurries all include Pt / C catalyst and ionomer; The mass fraction of Pt in the Pt / C catalyst is 20-60% and increases in sequence in the three catalyst slurries C1, C2 and C3; The mass ratio of the ionomer to the carbon carrier is 0.4-0.8 and decreases in sequence in the three catalyst slurries C1, C2 and C3.
6. A gradient cathode catalyst layer according to claim 4, characterized in that: The method for preparing the catalyst slurry comprises the following steps: The Pt / C catalyst and the ionomer solution are weighed in proportion, and the ethanol aqueous solution is added and mixed evenly, followed by ball milling and dispersion to obtain the catalyst slurry.
7. A gradient cathode catalyst layer according to claim 6, characterized in that: The ball milling time is 6-24h, and the ball milling speed is 100-300rpm.
8. A gradient cathode catalyst layer according to claim 6, characterized in that: The dispersion is carried out by ultrasonic dispersion, and the ultrasonic dispersion time is 10-60 minutes.
9. A membrane electrode, characterized in that: It includes a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively arranged on both sides of the proton exchange membrane; The cathode catalyst layer is a gradient cathode catalyst layer as described in any one of claims 1 to 8.
10. A proton exchange membrane fuel cell, characterized in that: Comprising the membrane electrode according to claim 9.
